The government and its impact on the stock market : evidence from Singapore - Ong, Lun Kuang (2013)
This paper analyses how the Singapore Government impacts the local stock market. In particular, we study the effects of Parliamentary activities and the annual financial budget announcement on stock return, volatility and liquidity. We find that Parliamentary activities do not have a significant impact on the volatility of the stock market as a whole. This implies that the uncertainty in policy changes during a Parliament session is very small, which can be explained by strong mandate the government possesses. For Financial Budget announcements, the returns are 0.125% higher in the period before the announcement as compared to the period after the announcement. This could be due to the optimism who anticipates that the government will implement well devised policies. Government investments in local companies have been widely studied and their findings are that they influence the growth and market values of these companies. When comparing the performances between government link corporations (GLCs) and non-GLCs, we find that the mean monthly returns of GLCs are on average 0.435% higher than non-GLCs. Profitability wise, ROE of GLCs is about 7.18% higher than non-GLCs. This implies that Temasek Holdings (government’s investment arm) is able to differentiate itself against other institutional owners with better corporate governance, reflecting higher GLCs market valuations. Comparing to Ang and Ding (2005), the ROE difference is lower by 2.92%, signalling a reduction in government support. Overall, our findings suggest that the government has an economically small yet significant impact on the stock market.